2021
DOI: 10.1111/jocn.16013
|View full text |Cite
|
Sign up to set email alerts
|

Rescripting—A grounded theory study of the contribution that fathers make to Family‐Based Treatment when a young person has anorexia nervosa

Abstract: Aim To present a grounded theory of the contribution that fathers make to family‐based treatment when a young person has anorexia nervosa. Background Research indicates a potential to improve outcomes by involving both parents in the treatment of anorexia nervosa. However, fathers are underrepresented both within treatment and research. Family‐based treatment requiring the involvement of both parents presents an opportunity to better understand the role of the father in treatment. Design Classic grounded theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 201 publications
(336 reference statements)
0
29
0
4
Order By: Relevance
“…Such vicious cycles can be worked on and interrupted without blaming one or the other parent. The clinical and empirical literature offers ample evidence of the unique and very significant role fathers play in their adolescent daughter’s recovery, including how their attendance in therapy is associated with improved treatment outcomes [ 59 , 68 ]. This information can be relayed to fathers to strengthen their motivation to join the family in its fight against the illness and improve their understanding of their daughter’s difficulties [ 63 , 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such vicious cycles can be worked on and interrupted without blaming one or the other parent. The clinical and empirical literature offers ample evidence of the unique and very significant role fathers play in their adolescent daughter’s recovery, including how their attendance in therapy is associated with improved treatment outcomes [ 59 , 68 ]. This information can be relayed to fathers to strengthen their motivation to join the family in its fight against the illness and improve their understanding of their daughter’s difficulties [ 63 , 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This component refers to the perceived symptoms of the disorder (Banerjee et al, 2022; Bear et al, 2021; Shiyanbola et al, 2018). Several studies reported that parents observed a range of symptoms associated with anorexia nervosa (Coelho et al, 2021; Cottee‐Lane et al, 2004; McMahon et al, 2022; Rosello et al, 2022; Thomson et al, 2014; Whitney et al, 2005; Williams, Russell‐Mayhew, et al, 2020). The most common symptoms observed included sudden changes in their child's eating behavior (e.g., dieting, eating “healthy,” becoming vegetarian, counting calories), physical appearance (e.g., weight loss), and increasing isolation from friends, family, and social activities (Coelho et al, 2021; Cottee‐Lane et al, 2004; McMullen, 2018; Rosello et al, 2022; Thomson et al, 2014; Williams, Russell‐Mayhew, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This category is associated with the understanding of the symptoms of their child's anorexia nervosa (Moss‐Morris et al, 2002; Severtson et al, 2008). Findings across studies indicated that parents had a poor understanding of anorexia nervosa (Coelho et al, 2021; Cottee‐Lane et al, 2004; Honey & Halse, 2005; Hoskins & Lam, 2001; Karlstad et al, 2021; Marinaci et al, 2021; McMahon et al, 2022; McMullen, 2018; Robinson et al, 2020; Sharkey‐Orgnero, 1999; Thomson et al, 2014; Tierney, 2005; Whitney et al, 2005; Williams, Russell‐Mayhew, et al, 2020). First, parents reported having difficulties recognizing the symptoms of anorexia nervosa (Honey & Halse, 2005; McMahon et al, 2022; Sharkey‐Orgnero, 1999; Thomson et al, 2014; Williams, Russell‐Mayhew, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations